Baby Booms and Asset Booms: Demographic Change and the Housing Market - FRANCKE, MARC; KOREVAAR, MATTHIJS (Journal of Finance, 2025)
ABSTRACTBased on centuries of data, we demonstrate that demographics have been a major, predictable driver of house prices. High birth rates 25 to 29 (60 to 64) years ago predict declining (rising) rent‐price ratios today. This pattern arises from age‐concentrated entry into and exit from homeownership affecting house prices, rather than changes in housing consumption that could also impact rents. We provide evidence for possible mechanisms: slow responses of other market participants to shifts in homeownership demand, and geographic segmentation between rental and owner‐occupied markets. Evidence for age‐dependent demand effects on yields of bonds and stocks is significantly weaker.